DRESSING DILEMMA: CREATING WEALTHY THROUGH DEHUMANIZING WOMEN AS ADVERTISING BAITS! THE BETRAYAL OF UBUNTUISM IN AFRICA - Gwakwa, Milton (European Scientific Journal, ESJ, 2014)
It is sad news! African culture is at crossroads. The creative elaboration of African tradition cannot be undermined by forces of globalization. The idea of a universal “modernity” as the pre-defined horror for all humanity has its consequences on African tradition. Viewers are literally exposed to ‘open geography’ of nude women who are used as advertising idols. The African ubuntu is at cross roads with these practices. The emergence of globalization and international trade into the continent have brought conflicting cultures that, many a time are at loggerheads with African ubuntuism and expected moral values. Competition in business, results in companies aggressively and (diplomatically) advertising their products using our innocent and desperate women as sexual objects, in order to increase their profits. This paper challenges the morality and ethicality of some business advertisements that exploit innocent women as is reflected in various media. A qualitative case based research philosophy was adopted and data was collected through observations, review of related literature, in-depth interviews and personal experiences. The findings of the study revealed that many advertising agencies employed innocent women to act as models in their advertising pro, most of which are physically, morally, culturally, spiritually and sometimes economically offensive and unfortunately this is exposing African ubuntuism to unprecedented levels of cultural decadence. At the same time the use of sexual imagery in advertising though obscene or immodest has seen businesses posting huge profits at the expense of ubuntuism-a social cost to Africa. The study recommends a new era in which African governments reformulate business policies that have an ubuntuist- flavour to avoid cultural decadence in favour of money and put measures to stop making the investor happier than thou.